Assessment of Selected Trace Metals, Physicochemical Parameters and Total Organic Carbon in Seawater along Tanjung Datu and Sematan Coastal Area - Farah Akmal, Idrus; Adriana, Christopher Lee; Jannatul Aisyah, Jamalulin (UNIMAS Publisher, 2024)
Tanjung Datu and Sematan coastal area are located at the west of Sarawak and has exposed to PanBorneo highway construction activities and annual haze, which can influence the concentration of trace metals, nutrients and organic carbon in the seawater. This study was specifically focused on trace metals (Al, Fe, Mn, Zn, Ni, Cu, Cr, Cd and Co), physicochemical parameters and total organic carbon (TOC) in seawater along the Tanjung Datu and Sematan coastal area. Trace metals were analysed using the Flame Atomic Absorption Spectroscopy (FAAS) and TOC analysis were using the TOC Analyser. The trends for trace metals concentration were Al (9.12 – 30.24 µM) >Fe (1.31 -8.24 µM) > Ni (0.61 – 1.17 µM) > Zn (0.57 – 0.67 µM) > Co (0.44 – 1.14 µM) > Cr (0.28 – 2.32 µM) > Mn (0.21 – 0.50 µM) > Cd (0.10 – 0.18 µM) > Cu (0.04 -1.01 µM). Physicochemical parameters values were 4.11 – 5.31 mg/L (DO), 30.49 – 31.53 °C (temperature), 0.52 - 13.0 NTU (turbidity), 7.97 – 8.89 (pH), 26.88 – 27.15 ppt (salinity), 46.7 – 47.78 mS/cm (conductivity), 27,365 – 27,628 mg/L (TDS), 0.01 – 0.05 mg/L (TSS), 0.02 – 0.28 µg/L (Chl-a), 3.07 - 3.90 mg/L (BOD5 ), 0.40 – 3.55 mg/L (phosphate), 0.01 – 0.05 mg/L (nitrate), 0.01 – 0.11 mg/L (nitrite) and 0.94 – 4.99 mg/L (ammonia). The range of TOC concentrations were 2.43 – 7.49 mg/L. The results showed that the potential sources of trace metals, nutrients (e.g. phosphate) in this area came from both atmospheric and land.